Ethical broadcasting standards in South African podcasting : an exploratory study - Nong, Kgabo Jonas (My University, 2025)
This study explored the ethical standards in South African podcasting. It analysed how podcasts navigate the principles of media ethics such as respect for privacy, harm avoidance, truthfulness, and the prevention of defamation. The study also explored how podcasting’s unregulated nature contributes to the dissemination of controversial content, including misogynistic remarks, derogatory statements about the LGBTQI+ community, and the objectification of women. The theoretical framework entailed two theories, namely; the Diffusion of Innovation and Media Policy Theory. This qualitative study used content analysis and semi-structured interviews for data collection from a total of five (5) radio presenters. The findings of this study indicate the significant gaps in ethical adherence in Podcast and Chill with MacG with content prioritising sensationalism over ethical considerations. The lack of regulation in podcasting is identified as a contributing factor to the perpetuation of harmful narratives impacting societal attitudes and public trust in media. The study concludes by recommending that South African podcasts adopt ethical practices that promote inclusivity, respect, and accountability. Furthermore, it suggests collaboration among regulatory bodies, content creators, and advocacy groups to ensure the sustainable growth of podcasting as a medium that reflects democratic values and fosters positive societal change.
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2025
Keywords: Chill with MacG; Podcast; Podcasting practice; Media regulation; Media ethics; Podcasting; Podcasting; Broadcasting; Mass media -- Moral and ethical aspects; Mass media -- South Africa; Broadcasting -- Standards -- South Africa